Pendekatan Filosofis Hukum Administrasi: Kajian Ontologi, Epistimologi, dan Aksiologi - Muklis Al'anam; Hendro Prabowo; Muhammad Fahlebvy (Fakultas Hukum Universitas Riau, 2025)
Administrative law philosophy is the foundation for understanding the nature, sources of knowledge, and objectives of administrative law in government administration practice. Ontologically, administrative law is viewed as a tool of public power that provides legitimacy and limits the authority of the government in carrying out administrative functions. From an epistemological perspective, administrative law is constructed through legislation, expert doctrine, court decisions, and government practices that evolve in line with social dynamics and community needs. Meanwhile, in the axial dimension, administrative law has values and objectives to ensure legal certainty, protect the rights of citizens, and realise transparent, accountable, and fair governance. This legal research uses a normative approach, with conceptual, legislative, and case studies. By examining administrative law through these three philosophical dimensions, it is hoped that a more comprehensive understanding will emerge and serve as a normative guideline for the government so that every administrative action is always in line with the principles of justice and democracy.